Inhibitory control, brain function and exercise in special populations - Costa, Kell Grandjean da (2019)
Inhibitory control is an executive function based on the prefrontal cortex (PFC) and is suggested to play a key role in healthy behaviors. Impairment of this cognitive function has been described in individuals with substance use disorder (SUD) and obesity. On the other hand, aerobic exercise and cardiorespiratory fitness has been shown to improve inhibitory control suggesting its potential role in preventing and treating impulsivity and unhealthy behaviors. Here we present four studies that investigated the interaction between inhibitory control, brain function, and exercise in individuals with substance use disorder and children with different body composition. In the first study, we review the chronic effects of aerobic exercise in individuals with SUD and propose a psychobiological model of exercise for future clinical trials in this population. On the second study, we showed the acute effects of aerobic exercise on inhibitory control and PFC oxygenation in individuals with SUD. On the third study, we showed how fat mass in children was associated with poorer foodspecific inhibitory control, independent of the cardiorespiratory fitness. And, in the fourth study, using an MRI scanner, we have identified the neural correlates associated with the food-specific inhibitory control in children. Together, our studies showed the potential benefits of keeping healthy behaviors, such as aerobic exercising and decreased levels of fat mass, on inhibitory control and brain function in special populations.